Towards a theory of aggregate output, income and economic inequalities determination in an Islamic economy - Tahir, Sayyid (International Islamic University Malaysia, 1989)
This paper builds a simple macroeconomic model for a closed Islamic economy. The model focuses on not only determination of aggregate output and income (as in conventional macroeconomics) but also the determination of inequality in the determination of aggregate disposable income between the poor (the have-nots) and the rich (the haves). Policy multipliers are also calculated. On the economic policy side, the results establish that Islamization of an otherwise non-Islamic economy through the introduction of zakah, will lead to increase in aggregate output and income but the end result may be either way for the degree of income equality.